Adaptive Fuzzy Integral Sliding Mode Control for Flexible Air-Breathing Hypersonic Vehicles Subject to Input Nonlinearity - Hu, Xiaoxiang; Wu, Ligang; Hu, Changhua; Gao, Huijun (Journal of aerospace engineering, 2013)
AbstractThis paper proposes a fuzzy integral sliding mode control strategy for flexible air-breathing hypersonic vehicles with input nonlinearity. Based on the complex nonlinear dynamics in the considered vehicles, a control-oriented model, which can retain the dominant features of the higher-fidelity model, is adopted for the control design. First, the T-S fuzzy approach is utilized to model the nonlinear dynamic of flexible air-breathing hypersonic vehicles, and the input nonlinearity model, which comprises dead-zones, sector nonlinearities, and actuator saturation, is considered. Then, based on the constructed T-S fuzzy model, a novel fuzzy integral sliding mode control method is proposed. This method can eliminate the reaching phase of the traditional sliding mode control by designing a novel sliding surface. Moreover, by the parallel-distributed compensation scheme, a sufficient condition is established to guarantee the global robust stability of the sliding mode dynamics in the specified surface in the presence of unmatched uncertainties and disturbance. The reachability of the specified sliding surface is guaranteed by an adaptive sliding mode controller under input nonlinearity. Finally, simulation results are given to show the effectiveness of the proposed control methods.